INFLAMATORNI MARKERI U POSLEDNJEM STADIJUMU RENALNOG OBOLJENJA U PACIJENATA NA HEMODIJALIZI - Abdel-Messeih, Phebe Lotfy; Alkady, Manal Mohamed; Nosseir, Neveen Mostafa; Tawfik, Mohamed Said (Journal of Medical Biochemistry, 2020)
Background: CXC chemokine ligand 16 (CXCL16) is an inflammatory chemokine that mediates renal infiltration of macrophages and activated T cells. Aim: To investigate serum levels of CXCL16 in patients undergoing hemodialysis and their correlation with other inflammatory markers such as C-reactive protein (CRP) and intact parathyroid hormone (iPTH). Methods: The study included 40 hemodialysis patients (22 males) and 40 age and gender-matched controls (24 males). Fasting blood sugar (FBS), urea, creatinine, calcium and inorganic phosphorous were assayed in participants using routine methods, glycosylated hemoglobin (HbA1c) by quantitative chromatographic spectrophoto metry, iPTH by chemiluminescent microparticle immuno assay, CRP by nephelometry and CXCL16 by ELISA technique. Results: Serum CXCL16, CRP, PTH, FBS, urea, and creatinine levels were significantly higher in hemodialysis patients compared to controls (p<0.00001). No statistically significant differences were observed between patients and controls for calcium, phosphorous, and HbA1c. Serum CXCL16 levels correlated positively with CRP (r=0.956, p<0.00001) and iPTH (r=-0.403, p<0.001). Hemodialysis patients (diabetics or hypertensives) had significantly higher CXCL16 levels compared to non-diabetics or nonhypertensives. Conclusions: High levels of serum CXCL16, CRP and iPTH reflect the inflammatory status of hemodialysis patients and help avoid complications. Serum CXCL16 could be used as a biomarker together with CRP in these patients.